Leprosy reaction in patients of health centers from the Planning Area 3.2. of Rio de Janeiro Municipality - Silva, Slete Ferreira da (2007)
Leprosy reaction is one of the greatest problems in leprosy control programs. During treatment or even after end of treatment, many patients return to the healthcare unit with reactions characterized by inflammatory process, pain, malaise and at times a increased grade of incapacity. The inability to estimate the magnitude of leprosy reaction in the Rio de Janeiro municipality difficulted the planning of effective leprosy control program. This study demosntrated the frequency of reactions in patients from the basic health units who were treatedwith multidrugtherapy (MDT) from 1991 to 2004. The study also characterized the socio-demographic and clinical profile associated to the occurrence of reactional episodes in patients of the study. This is a cohort non-concurrent study using as data source 667 medical charts. The majority of leprosy patients were between 35 and 54 year, they were mostly married womem (52.3%) with low schooling levels. During the evaluation period 43.5% patients presented reactions. The reaction rate was higher among: males (49.4%, n=157, patients with borderline or lepromatous forms, positive bacillary index, grade of incapacity zero and one and patients who received over 12 doses of treatment. These characteristics should be taken into account when caring for leprosy patients, so that early detection of reactions and initiation of specific treatment may diminish the onset of physical incapacities and sequels.